Fait divers ou avatar de l’histoire du fils prodigue : "Niespodzianka" de Rostworowski et "Le Malentendu" de Camus - Jakubczuk, Renata (2023)
The current article – focused on two plays about the killing of a son by his family – has a double objective: firstly, it questions the probable source of a folkloric story of the prodigal son, and secondly, it places side by side theater plays based on a legendary theme. After presenting the playwrights, Karol Hubert Rostworowski and Albert Camus, as well as the terminological propositions of Eric Durnez, the article analyses the convergences and divergences that we find in using the subjects from chronicles quasi mythical.
Keywords: Camus Albert; Rostworowski Karol Hubert